Perancangan Sistem Informasi Manajemen Keuangan pada Masjid Al Mustaqim Helvetia Tengah Berbasis Web dengan Metode Rapid Application Development (RAD) - Muhammad Farhan Mahendra; Demonius Sarumaha; Saiful Amir (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
Financial management in most mosques, including Al Mustaqim Mosque in Helvetia Tengah, is still carried out manually using paper-based cash books and reports, making it prone to recording errors, difficult to trace, and lacking transparency for both worshippers and mosque administrators. This research aims to design and build a web-based Financial Management Information System for Al Mustaqim Mosque in Helvetia Tengah so that the recording of income, expenses, and financial reporting can be carried out in a computerized, accurate, and transparently accessible manner for the public. The development method used is Rapid Application Development (RAD), consisting of five stages: business modeling to map the mosque’s financial management business process, data modeling to design the transaction and user database structure, process modeling to translate the business process into system functions, application generation to build the application using the Flask framework. The result of this research is a web-based information system built using Flask, SQLAlchemy, and an SQLite database, equipped with a public portal for financial transparency to worshippers, an admin dashboard, CRUD (create, read, update, delete) operations for income and expense transactions, Based on the implementation and testing results, it can be concluded that the developed system is able to improve the efficiency of recording time, the accuracy of balance calculations, and the transparency of mosque financial management compared to the previously used manual recording method.